Impact of Digital Library Services on User Behavior at Unisba Library - Septiandi, Yusep; Agus Rusmana; Yunus Winoto (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Abstract.The advancement of digital technology has significantly influenced various sectors, including the access and management of academic information in higher education. As central hubs of information, university libraries need to adapt by implementing innovative digital services. At Bandung Islamic University (UNISBA), this transformation is visible through developments such as the SiPINTAR application and an online repository system. This study aims to explore and analyze the transformation of user behavior in accessing academic information after the implementation of digital services. A descriptive qualitative approach was employed, involving interviews with seven active students and two librarians, fitted by documentation of library services. The findings indicate that students generally prefer digital services due to their convenience and accessibility. However, challenges remain, particularly in terms of digital literacy and the limited scope of available digital collections. The study concludes that while the digitization of library services at UNISBA has enhanced access to academic information, consistent user education and continuous service improvement is vital to ensure optimal utilization.